2010
DOI: 10.1007/s00134-010-1983-5
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 2 and 4: initiators of non-septic inflammation in critical care medicine?

Abstract: Purpose Although the role of Toll-like receptors (TLRs) in bacterial infection and sepsis is well characterized, recent studies have also shown that TLR4 and TLR2 can play an important role in contributing to acute inflammatory processes and organ dysfunction in settings in which LPS or other bacterial products are not present. This review presents not only insights into pathophysiologic mechanisms that contribute to organ dysfunction and outcome in critical illness, but also direct therapeutic approaches to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 82 publications
1
75
0
1
Order By: Relevance
“…The increased expression of TLR2, TLR4 mRNA -widely distributed not only in immune but also in non-professional antigen presenting cells, such as stromal prostatic cells (Fibbi et al 2010) -suggests the activation of both innate and specific immune responses. Recent studies have shown that TLR2, TLR4 can play an important role in initiating a proinflammatory cascade, even in clinical settings in which microbial ligands are not present (Lorne et al 2010). Indeed, in our model of MetS-associated prostate inflammation, no nitrites and leukocyte esterase were detected in the urine.…”
Section: Discussionmentioning
confidence: 55%
“…The increased expression of TLR2, TLR4 mRNA -widely distributed not only in immune but also in non-professional antigen presenting cells, such as stromal prostatic cells (Fibbi et al 2010) -suggests the activation of both innate and specific immune responses. Recent studies have shown that TLR2, TLR4 can play an important role in initiating a proinflammatory cascade, even in clinical settings in which microbial ligands are not present (Lorne et al 2010). Indeed, in our model of MetS-associated prostate inflammation, no nitrites and leukocyte esterase were detected in the urine.…”
Section: Discussionmentioning
confidence: 55%
“…Inflammation is initiated by the presence of pathogen-associated molecular patterns (PAMPs) or danger-associated molecular patterns (DAMPs) -commonly intracellular components released via tissue damage [3][4][5] . These conserved molecular motifs bind pattern-recognition receptors (PRRs) such as Toll-like receptors (TLRs) found on epithelial cells, endothelial cells and those of the innate immune system, to trigger common downstream intracellular signaling pathways 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Without proper regulation, these mechanisms inflict serious damage, and even death, on the host. Improper activation of TLR4 contributes to inflammatory diseases such as acute lung injury (44) and autoimmune diseases like rheumatoid arthritis (45). It is no wonder that hosts balance TLR4 effects to ensure both pathogen clearance and host health.…”
Section: Discussionmentioning
confidence: 99%